PERFORMANSI ALAT PENGASAPAN IKAN DENGAN SISTEM ROTARI HORIZONTAL - Perdana, Mastariyanto; Hafni, Hafni; Yulianti, Lusi; Romi, Romi; Alfith, Alfith; Pratiwi, Putri; Nurzal, Nurzal (Jurnal Teknologi dan Vokasi, 2024)
One of the fish preservation techniques that are widely used today is the smoking technique. In general, the smoking process was still traditional and used a conventional oven. This method is an easy way to smoke fish. The purpose of this study was to determine the efficiency of the fish smoking device using a horizontal rotary system. This smoking device consists of a smoking chamber, a furnace, a rotary catfish holder, a DC motor, gears, and a chain. The capacity of this rotary system smoker is 9 kg of wet fish. The fish used in this study were catfish and skipjack fish. This smoking uses the result of burning cinnamon. Cinnamon will produce smoke which is useful for smoking fish. The weight of wet fish in one smoke in this study was 8 kg. The smoking method has a standard ratio of wet fish weight to dry fish weight of 4: 1. For smoking catfish, after smoking for 2 hours at a temperature of 80 oC - 90 oC, the weight of catfish becomes 2 kg. For smoking skipjack tuna, after smoking for 2.5 hours at a temperature of 80 oC - 90 oC, the weight of skipjack tuna becomes 2 Kg. From the test results, it can be concluded that the rotary smoking system is very good for use as a fish smoking tool because it has a high enough efficiency compared to traditional tools such as ovens where the traditional smoking method takes 36 hours and the oven system smoking method takes as long as 12 hours.